Aggregation State and Neurotoxic Properties of Alzheimer β-Amyloid Peptide - Mohamed, Amany; Cortez, Leonardo; Posse de Chaves, Elena (Current Protein and Peptide Science, 2011)
Alzheimer's disease (AD) represents the most common form of senile dementia and represents a tremendous health problem as the world population is aging. AD is characterized by the accumulation of amyloid β-peptide (Aβ) in the brain and the loss of cholinergic neurons in the basal forebrain. Accumulation of soluble and insoluble assemblies of Aβ in the brain is a crucial event in AD pathogenesis and the presence of amyloid plaques in the brain is required for definitive identification of AD. Yet, there is no correlation between amyloid plaques and the degree of dementia. In the past two decades researchers have devoted their effort to study and explain the mechanisms involved in the pathology of this devastating disease. Studies from different areas of the natural and medical sciences have provided important information towards the elucidation of some of the pathological processes that take place in AD. An aspect of crucial importance is the aggregation state of Aβ peptide and its role in neuropathology. Here, we discuss recent studies aimed at the identification of Aβ protein aggregates, the characterization of their toxic potential and the development of therapeutic strategies that target Aβ aggregation.
Keywords: post-Golgi secretory